Analisis Keuntungan Pedagang Beras Sebelum dan Sementara Pembangunan Gedung Baru Pasar Sentral Laino Kota Raha Kabupaten Muna - Halida, Fayadh Mahdi; Surni, Surni; Dirgantoro, Muhammad Arief (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aims to (1) analyze the profit of rice traders before and while the construction of a new building in Pasar Sentral Laino Kota Raha, Muna Regency, (2) analyze the differences in the profits of rice traders before and while the construction of a new Gedung Sentral Laino Kota Raha Muna Regency. This research was conducted in January-March 2017 at the Laino Central Market, Kota Raha, Muna Regency. The sample in this study amounted to 23 people. Types and sources of research data, namely primary and secondary data. Research data collection techniques, namely through (1) observation, (2) interviews, (3) literature. The research variables consisted of (1) characteristics of rice traders, including: age, education level, sex and duration of trading, (2) trade characteristics, including: type and origin of rice, purchase and sales volume (Kg / Quarter), purchase price and sales (IDR / Kg), marketing costs (IDR) and profits (IDR / Quarter). The results of the study showed (1) The average profit of rice traders before construction was IDR 4,984,696 / Quarter and the average profit of rice traders while construction was IDR 3,791.304 / Quarter, (2) there were significant profit differences.